Resonance analysis of fan blade design using Finite Element Method - Dedik Romahadi; Rikko Putra Youlia; Himawan S. Wibisono; Muhammad Imran (Universitas Mercu Buana, 2024)
Fan motors move liquids, such as air, in the gas phase from one place to another. The frequency of the fan blades, which are the main components of the fan motor, can vary. It is crucial to know the frequencies of each fan blade to avoid design failures caused by resonance. This research analyzes the effect of differences in the angle and number of blades on the natural frequency of the fan to avoid resonance with the motor rotation frequency. Modeling and simulation using the finite element method in the Solidworks application are used to determine the natural frequencies of the fan. Fans come in various configurations, with blades ranging from two to four, and blade pitch can be 25°, 30°, or 40°. Variations in the number of fan blades and changes in blade pitch show that the low mode shape does not affect the natural frequency, while the high mode has a negligible effect. The natural frequency of fan blades 2, 3, and 4 exhibits variations when operated with motors running at 25, 35, or 50 Hz. The findings imply that the fan blades' inherent frequency does not align closely with the motor rotational frequency, indicating that the design is safe.